Unelius Barkborreexperiment 2022 - Svensson, Andreas; Unelius, Rikard; Schlyter, Fredrik; Hubner, Anton; Ganji, Suresh (Linnaeus University, 2026)
Capture data of bark beetles from experiment with combination of different lures

Fångstdata på barkborrar från experiment med kombination av olika attrahenter
Unelius Bark Beetle experiment 2022
Keywords: Scolytidae; barkborrar; Organic Chemistry; Organisk kemi; Ecology; Ekologi; Biochemistry; Biokemi